Alcohol use and alcohol-related harm in rural and remote communities: protocol for a scoping review - Paul Kurdyak; Erik Loewen Friesen (BMJ Open)
Introduction Alcohol-related harm is a major public health concern and appears to be particularly problematic in rural and remote communities. Evidence from several countries has shown that the prevalence of harmful alcohol use and alcohol-attributable hospitalisations and emergency department visits are higher in rural and remote communities than in urban centres. The extents of this rural–urban disparity in alcohol-related harm as well as the factors that mediate it are poorly understood. The objective of this scoping review is to synthesise the international research on the factors that influence the prevalence or risk of alcohol-related harm in rural and remote communities. This will help to clarify the conceptual landscape of rural and remote alcohol research and identify the gaps in knowledge that need to be addressed.Methods and analysis This scoping review will access published literature through search strategies developed for Medline, PsycINFO, Embase, CINAHL and Sociological Abstracts. There will be no date, country or language restrictions placed on the search. Title and abstract, followed by full-text screening, will be conducted by two independent reviewers to evaluate all identified articles against a set of prespecified inclusion and exclusion criteria. Data from selected articles will be extracted and compiled into a final manuscript that adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews checklist guidelines.Ethics and dissemination The results of this review will be helpful in guiding future research on rural and remote alcohol use and alcohol-related harm, which will inform more effective, evidence-based public health strategies to reduce alcohol-related harm in rural and remote communities. The results will be disseminated via field-specific conference presentations and peer-reviewed publication.